Sudden cardiac and sudden unexpected death related to antipsychotics: A meta‐analysis of observational studies. Issue 3 (20th November 2015) - Salvo, F; Pariente, A; Shakir, S; Robinson, P; Arnaud, M; Thomas, SHL; Raschi, E; Fourrier‐Réglat, A; Moore, N; Sturkenboom, M; Hazell on behalf of Investigators of the ARITMO Consortium, L; ,
Abstract : To estimate the risk of sudden cardiac death (SCD) or sudden unexpected death (SUD) related to individual antipsychotics, a meta‐analysis of observational studies was performed. Adjusted odds ratio (OR) of SCD/SUD with 95% confidence intervals (CI) were extracted and pooled; heterogeneity was studied using Q statistic and I 2 index, and its potential causes (e.g., hERG blockade potency) explored using meta‐regression. Two cohort (740, 306 person‐years) and four case–control (2, 557 cases; 17, 670 controls) studies, investigating nine antipsychotics, were included. Compared with nonusers, the risk was increased for quetiapine (OR = 1.72, 95% CI: 1.33–2.23), olanzapine (OR = 2.04, 1.52–2.74), risperidone (OR = 3.04, 2.39–3.86), haloperidol (OR = 2.97, 1.59–5.54), clozapine (OR = 3.67, 1.94–6.94), and thioridazine (OR = 4.58, 2.09–10.05). Heterogeneity was found (Q = 20.0, P = 0.01; I 2 = 60.0%), and the increasing mean hERG blockade potency ( P = 0.01) accounted for 43% of this. The SCD/SUD risk differed between individual antipsychotics, and mean hERG blockade potency could be an explanatory factor. This should be considered when initiating antipsychotic treatment.